Ni-rich Nitrides ANNi3 (A = Pt, Ag, Pd) in Comparison with Superconducting ZnNNi3 (Journal of Scientific Research, 2011)
This article reports on the elastic, electronic and optical properties of predicted Ni-rich nitrides ANNi3 (A= Pt, Ag, Pd) in comparison with isostructural superconducting counterpart ZnNNi3. We have used first-principles density functional theory (DFT) with generalized gradient approximation (GGA). The independent elastic constants (C11, C12, and C44), bulk modulus B, compressibility K, shear modulus G, and Poisson’s ratio υ, as well as the band structures, total and partial densities of states and finally the optical properties of ANNi3 have been calculated. The results are then analyzed and compared with those of the superconducting ZnNNi3. The electronic band structures of the three compounds show metallic behavior with a high density of states at the Fermi level in which Ni 3d states dominate just like the superconducting ZnNNi3. Analysis of Tc expression using available  parameter values suggests that the three compounds are less likely to be superconductors. Optical reflectivity spectra indicate that all the compounds have the potential to be used as a coating to remove solar heating.Keywords: ANNi3; Ab initio calculations; Elastic properties; Electronic band structure; Optical properties.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i1.9026J. Sci. Res. 4 (1), 1-10 (2012)